Distribution of β-lactamase genes of Klebsiella pneumoniae isolates in Zhejiang province, China, and regulation of gene expression - Zhao, Jin-Fang; Wang, Qiang; Ge, Yu-Mei; Tan, Pan-Li; Chen, Yi-Min; Yan, Jie (Archives of Biological Sciences, 2017)
Klebsiella pneumoniae is a common causative agent of nosocomial infections with a high level of resistance toward β-lactam antibiotics. Our previous study showed that TEM-1 and SHV-11 are the predominant β-lactamase-encoding genes of K. pneumoniae isolates in the Zhejiang area, China. In this study, more clinical K. pneumoniae isolates were collected for detecting their β-lactamase-encoding gene profiles by PCR and sequencing. qRT-PCR was then performed to determine the role of cefotaxime or penicillin in low concentrations to induce the β-lactamase gene expression of K. pneumoniae isolates. Moreover, the K. pneumoniae isolates were pretreated with closantel (CLO), a histidine kinase inhibitor, before antibiotic treatment, and qRT-PCR and the β-lactamase phenotype confirmatory test were then applied to determine the effect of CLO on the expression of the β-lactamase genes. The results showed that, except for KPC-2, the 1/4 MIC cefotaxime or penicillin induced significant mRNA elevation of the TEM-1, CTX-M-14, SHV-11 and OXA-1 β-lactamase genes, but this induction could be inhibited by CLO. After pretreatment with CLO, 78.4 81.4% of the β-lactam-resistant isolates became sensitive and the positive rate of the β-lactamase production phenotype in the isolates was decreased from 100% to 27.1%. The data indicate that TEM-1 (70.7%), SHV-11 (64.2%) and CTX-M-14 (40.5%) are the predominant β-lactamase genes of the K. pneumoniae isolates in Zhejiang and sublethal dosage of β-lactam antibiotics can induce the β-lactamase gene expression of K. pneumoniae through histidine kinase-mediated two-component signaling systems. https://doi.org/10.2298/ABS160512112Z Received: May 12, 2016; Revised: July 21, 2016; Accepted: August 15, 2016; Published online: October 31, 2016 How to cite: Zhao JF, Wang Q, Ge YM, Tan PL, Chen YM, Yan Jie. Distribution of β-lactamase genes of Klebsiella pneumoniae isolates in Zhejiang province, China, and regulation of gene expression. Arch Biol Sci. 2017;69(3):399-407.